Penerapan Metode First Come First Served Pada Sistem Informasi Layanan Reservasi Futsal Berbasis Website - Aji, Rahmat Widodo; Darusalam, Ucuk (STMIK Budi Darma, 2022)
Leo futsal is a business that provides facilities for futsal sports that was established in 2019. The high interest in every day makes Leo futsal overwhelmed because the futsal field rental system is still conventional where customers still have to go to the location to check the schedule the field is still vacant or the customer contacts the managers' WhatsApp to find out the available fields and to notify the field tenants if the rental time has run out, the field manager must look at the wall clock several times. That's what made the writer decide to design a website-based futsal field rental information system with the aim of making it easier for field managers and making it easier for customers to see the empty field schedule. The researcher designed the futsal field reservation information system using the first come first served method with the system development method using the waterfall method.